2018
DOI: 10.1530/joe-17-0457
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection of dapagliflozin and vildagliptin in rats with cardiac ischemia-reperfusion injury

Abstract: Sodium-glucose cotransporter 2 inhibitor (SGLT2-i) effects on cardiac ischemia/reperfusion (I/R) injury are unclear. Unlike SGLT2-i, dipeptidyl peptidase 4 inhibitors (DPP4-i) have shown effective cardioprotection in cardiac I/R injury. We aimed to investigate whether SGLT2-i reduces myocardial dysfunction and myocardial injury to a greater extent than DPP4-i in obese insulin-resistant rats with/without cardiac I/R injury. The high-fat (HF) diet-induced obese insulin-resistant rats were divided into 4 groups a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
78
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 39 publications
6
78
0
Order By: Relevance
“…Based on these previous findings, it is possible that, in our current study, selective SGLT2-inhibitors exerted direct cardioprotective effects, although further studies will be needed in order to investigate the effects of those pharmacological agents on cardiac NHE under diabetic insulin-resistant conditions as well as on cardiac fibrosis through histopathological analyses. Regardless, the present study investigated the transient local direct effects of SGLT2inhibitors on the cardiac tissue during the acute phase of IRI; our findings therefore do not conflict with the consistent cardioprotective results from other in vivo experimental studies [44,[49][50][51][52][53][54][55][56] or clinical trials [31][32][33], all of which investigated the systemic effects of SGLT2-inhibitors over a longer period. Furthermore, the present findings suggest that potential mechanisms underlying the cardiovascular benefits of SGLT2-inhibitors may depend largely on the systemic inter-organ network, including cardiorenal syndrome [57][58][59].…”
Section: Discussionsupporting
confidence: 52%
“…Based on these previous findings, it is possible that, in our current study, selective SGLT2-inhibitors exerted direct cardioprotective effects, although further studies will be needed in order to investigate the effects of those pharmacological agents on cardiac NHE under diabetic insulin-resistant conditions as well as on cardiac fibrosis through histopathological analyses. Regardless, the present study investigated the transient local direct effects of SGLT2inhibitors on the cardiac tissue during the acute phase of IRI; our findings therefore do not conflict with the consistent cardioprotective results from other in vivo experimental studies [44,[49][50][51][52][53][54][55][56] or clinical trials [31][32][33], all of which investigated the systemic effects of SGLT2-inhibitors over a longer period. Furthermore, the present findings suggest that potential mechanisms underlying the cardiovascular benefits of SGLT2-inhibitors may depend largely on the systemic inter-organ network, including cardiorenal syndrome [57][58][59].…”
Section: Discussionsupporting
confidence: 52%
“…This is consistent with our observation that EMPA restored mtDNA damage, mtDNA/nDNA ratio and restored PGC1‐α expression, indicating that the effects of SGLT2i on mitochondrial biogenesis can be translated to the non‐diabetic failing heart. Third, the changes in PDH activity and the expression levels of CPT1, GLUT4 and PDK4 observed by us and by others, suggest that the myocardial capacity to oxidize glucose and fatty acids is improved by EMPA. Verma et al .…”
Section: Discussionsupporting
confidence: 49%
“…Second, several studies have suggested that SGLT2i can restore cardiac mitochondrial dysfunction. Indeed, the SGLT2i dapagliflozin restored cardiac PGC1‐α in pre‐diabetic rats . PGC1‐α is a critical mediator of mitochondrial biogenesis and the reductions in PGC1‐α are thought to contribute to mitochondrial dysfunction observed in HF.…”
Section: Discussionmentioning
confidence: 99%
“…Another SGLT2i, dapagliflozin significantly improved LV EF in a HF model that was creased by coronary artery ligation/reperfusion on high-fat diet-induced pre-diabetic Wistar rats. The biological mechanisms on cardioprotection of 4-week dapagliflozin were suggested from a combination of modulation of mitochondrial DRP1, caspase 3, and lipid peroxidation [30]. The LV EF was not significantly improved by 12-week empagliflozin in our hypertensive heart failure model.…”
Section: Discussionmentioning
confidence: 68%